Morpho-syntactic features of Mahri language in Yemen: An ethno-narrative study / Saeed Saad Najadan Al-Qumairi - Al-Qumairi, Saeed Saad Najadan (2013)
Due to the requirement of UNESCO (1993) which recommended by adopting the ‘Endangered languages Project’, the current study aims at analyzing the morpho-syntactic features of Mahri language. The tribal language of the minority group people in Yemen, this language deliberately receives a great deal of ignorance which may lead to the extinction of this oral heritage, Simeone-Senelle (1997) and Rubin (2010). Certainly, this research report is limited to demonstrate the interface between morphology and syntax, focusing on how the formal features in a language are embedding in words, creating relationship among phrasal structures and affecting the typological word order of the sentences. To relate Mahri with the ideology and the sociocultural contexts in a society, this report conducts two methods the narrative approach and ethnographic approach, where the native speaker researcher randomly selects the naturalistic data and sentential structures from typical written texts precisely, storytelling and lyric poems. Establishing Chomsky’s X-bar Theory as the study analytical tool, the results show that indeed Mahri is highly morphological language which composes different types of agreement features such as gender, number and person features and in addition to syntactic features which represent by nominative, accusative, dative and genitive cases. Regarding to the fact that there is no asymmetry between subjects and predicates, it is found that the syntactic word order in Mahri language is deemed to be optional. Overall, the findings of the study are hoped to contribute and add new facts to the missing linguistic knowledge in field of linguistics and Semitic studies which Mahri is a single branch of this largest group in Western Asia.